T cell dysfunction in elderly ARDS patients based on miRNA and mRNA integration analysis - Mitsuyama, Yumi; Matsumoto, Hisatake; Togami, Yuki; Oda, Sayaka; Onishi, Shinya; Yoshimura, Jumpei; Murtatsu, Arisa; Ito, Hiroshi; Ogura, Hiroshi; Okuzaki, Daisuke; Oda, Jun (Frontiers in Immunology, 2024)
Background: Acute respiratory distress syndrome (ARDS) is respiratory failure that commonly occurs in critically ill patients, and the molecular mechanisms underlying its pathogenesis and severity are poorly understood. We evaluated mRNA and miRNA in patients with ARDS and elucidated the pathogenesis of ARDS after performing mRNA and miRNA integration analysis.In this single-center, prospective, observational clinical study of patients with ARDS, peripheral blood of each patient was collected within 24 hours of admission.Sequencing of mRNA and miRNA was performed using whole blood from the ARDS patients and healthy donors.Results: Thirty-four ARDS patients were compared with 15 healthy donors. Compared with the healthy donors, 1233 mRNAs and 6 miRNAs were upregulated and 1580 mRNAs and 13 miRNAs were downregulated in the ARDS patients. For both mRNA and miRNAtargeted mRNA, canonical pathway analysis showed that programmed death-1 (PD-1) and programmed cell death ligand 1 (PD-L1) cancer immunotherapy pathway was most activated and the Th2 pathway was most suppressed. For mRNA, the Th1 pathway was most suppressed. miR-149-3p and several miRNAs were identified as upstream regulators.Th2 pathway through miRNA interference action of mRNA. Integrated analysis of mRNAs and miRNAs showed that T cells were dysfunctional in ARDS patients.